King's Parkinson's Disease Pain Scale for Assessment of Pain Relief Following Deep Brain Stimulation for Parkinson's Disease. Issue 6 (2nd April 2018) - DiMarzio, Marisa; Pilitsis, Julie G.; Gee, Lucy; Peng, Sophia; Prusik, Julia; Durphy, Jennifer; Ramirez‐Zamora, Adolfo; Hanspal, Era; Molho, Eric; McCallum, Sarah E.
Abstract : Objective: Pain is a prevalent and debilitating nonmotor symptom of Parkinson's disease (PD) that is often inadequately managed. Deep brain stimulation (DBS) has been shown to relieve pain in PD but an effective method of identifying which types of PD pain respond to DBS has not been established. We examine the effects of DBS on different types of PD pain using the King's Parkinson's disease pain scale (KPDPS), the only validated scale of PD pain. Methods: We prospectively followed 18 PD patients undergoing subthalamic nucleus (STN) or Globus pallidus interna (GPi) DBS. Subjects completed the KPDPS, low back disability index (LBDI), and McGill pain questionnaire (MPQ), preoperatively and at six months postoperatively. Subjects underwent the unified Parkinson's disease rating scale‐III (UPDRS‐III) with preoperative scores ON medication and postoperative scores ON medication/DBS stimulation. Results: Of the 18 patients, a total of 12 subjects had STN DBS and 6 had GPi DBS. As a group, subjects showed improvement in total KPDPS score at six‐month postoperative follow‐up ( p  = 0.004). Fluctuation and nocturnal pain were most significantly improved ( p  = 0.006, 0.01, respectively). Significant improvements were found in fluctuation‐related pain domain following GPi DBS. Conclusions: In this pilot study, we are the first group to employ KPDPS to monitor pain relief following DBS in PD patients. We demonstrate that fluctuation‐related pain and nocturnal pain significantly improve with DBS. Use of the KPDPS in the future will allow better understanding of how STN and GPi DBS treat PD pain over time.